The only thing to fear - Richmond, Caroline Tung (Scholastic Press, 2014)
It has been nearly eighty years since Hitler's armies won World War II, and sixteen-year-old Zara St. James lives in the Shenandoah hills, part of the Eastern American Territories, under the rule of the Nazis--but a resistance movement is growing, and Zara, who dreams of freedom, may be the key to its success.